Standarisasi Manajemen Risiko ISO 31000: Tantangan dan Strategi Implementasi pada PT. Telkom Indonesia: Penelitian - Afrila Mulyati Siregar; Kariono; Ade Rani; Dara Yuliani; Natalin Pepayosa Sembiring; Chika Naibaho; Febri Sabrina Hasibuan; Istiqomah Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the challenges and strategies for implementing ISO 31000: 2018 Risk Management standardization in PT. Telkom Indonesia. It is characterized by globalization that supports the advancement of information and Communication Technology in the field of telecommunications industry. PT. Telkom Indonesia as one of the major players in this industry, is required to be able to effectively manage risks in order to ensure the continuity of operations and services to customers. Standardized risk management is an important aspect that can help companies in identifying, analyzing, and addressing potential risks that can interfere with business performance. Using the literature review method, this study identifies inhibiting factors such as operational complexity, administrative burden, and dependence on IT infrastructure. The results showed that PT. We have adopted ISO 31000: 2018 through policy updates, risks faced, employee training, and ERM application development. This has a positive impact such as reducing GHG emissions, increasing customer satisfaction, and fulfilling corporate governance. However, issues such as security risks and costs must still be considered. The study provides recommendations and suggestions to reduce risks and strengthen system integration in order to achieve business sustainability.